1996
DOI: 10.1063/1.116950
|View full text |Cite
|
Sign up to set email alerts
|

Observation of misfit dislocations at the InxGa1−xAs/GaAs interface by ballistic-electron-emission microscopy

Abstract: Articles you may be interested inStructural and optical investigations of high quality InGaAs/InAlAs short period superlattices grown on an InGaAs quasisubstrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The application of BEEM to semiconductor heterostructures was proposed by Henderson et al 4 and has been demonstrated in several systems including InAs/GaAs, 5 Si p-n junctions, 6 AlAs/GaAs, 7 SiGe strained layers, 8 and Al x Ga 1Ϫx As/GaAs heterostructures. 9,10 More recently, the capabilities of BEEM have been exploited in studies of dislocations in In x Ga 1Ϫx As/GaAs, 11 ordered-Ga x In 1Ϫx P/GaAs heterostructures, 12 InAs quantum dots, 13 and InAs/AlSb heterostructures. 14 We have previously shown that BEEM spectra from single Al x Ga 1Ϫx As barrier samples 9 are consistent with measurements of the GaAs/Al x Ga 1Ϫx As conduction-band offset (⌬E C ͒ in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The application of BEEM to semiconductor heterostructures was proposed by Henderson et al 4 and has been demonstrated in several systems including InAs/GaAs, 5 Si p-n junctions, 6 AlAs/GaAs, 7 SiGe strained layers, 8 and Al x Ga 1Ϫx As/GaAs heterostructures. 9,10 More recently, the capabilities of BEEM have been exploited in studies of dislocations in In x Ga 1Ϫx As/GaAs, 11 ordered-Ga x In 1Ϫx P/GaAs heterostructures, 12 InAs quantum dots, 13 and InAs/AlSb heterostructures. 14 We have previously shown that BEEM spectra from single Al x Ga 1Ϫx As barrier samples 9 are consistent with measurements of the GaAs/Al x Ga 1Ϫx As conduction-band offset (⌬E C ͒ in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Both of the As-rich related defects and the misfit dislocations introduce acceptor centers, which will trap electrons and degrade the mobility. [13,14] On the other hand, different growth temperatures for the InGaAs and InAlAs layers introduce longer growth interruption time, which leads to an excessive density of undesired background impurities right at the InAlAs/InGaAs interface and degrades the 2DEG properties. It is advantageous to find a common growth temperature for both InAlAs and InGaAs layers.…”
Section: Methodsmentioning
confidence: 99%
“…Observable strain relief occurs only if this "excess" stress exceeds a critical value, which, however, depends on temperature. Lee et al 15 used ballistic electron emission microscopy ͑BEEM͒, atomic force microscopy ͑AFM͒, transmission electron microscopy ͑TEM͒ and scanning tunneling microscopy ͑STM͒ on InGaAs/ GaAs interfaces, and found cross-hatch patterns that originate from misfit dislocations. Belk et al 16 used STM to study misfit-dislocation induced lattice distortions of the epilayer for InAs thin films grown on GaAs͑110͒.…”
Section: Preliminariesmentioning
confidence: 99%
“…[11][12][13][14] The incoherent mechanisms, on the other hand, are observed in systems with small mismatch, and involve formation of interfacial defects such as misfit dislocations and/or dislocation arrays, which, however, do not destroy the planar morphology of the film, resulting in a layer-by-layer 2D growth-mode. 6,[15][16][17][18][19][20] In cases of very large mismatch both classes of mechanisms may become operative. While strain relaxation processes destroy the uniformity of the strain fields and thus their beneficial role in some device applications, they can have a desirable effect in other applications such as in assisting the self-organization of 3D islands in order to form regular arrays of quantum dots.…”
Section: Introductionmentioning
confidence: 99%